2015
DOI: 10.1103/physrevb.92.094104
|View full text |Cite
|
Sign up to set email alerts
|

Stable xenon nitride at high pressures

Abstract: Nitrides in many ways are fascinating since they often appear as superconductors, high energy density and hard materials. Though there exist a large variety of nitrides, noble gas nitrides are long missing in nature. Pursuit of noble gas nitrides has therefore become the subject of topical interests, but remains as a great challenge since molecular nitrogen (N 2 , a major form of nitrogen) and noble gases are both inert systems and do not interact at normal conditions. We show through a swarm structure searchi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…These nitrogen species have various structural forms ranging from single atom (N) to molecular (N 2 , N 3 , N 4 , N 5 , N 6 ) units and polynitrides 13 17 . To note, these stable nitrides have a variety of intriguing properties, such as superconductivity (MoN) 13 , high-energy density (LiN 3 , NaN 3 ) 14 , and high hardness (WN 2 ) 15 , as well as extraordinary chemical and thermal stability (Xe-N) 16 . These nitrides aroused our significant interest in the field of exploring new HP nitrogen species and their potential remarkable properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These nitrogen species have various structural forms ranging from single atom (N) to molecular (N 2 , N 3 , N 4 , N 5 , N 6 ) units and polynitrides 13 17 . To note, these stable nitrides have a variety of intriguing properties, such as superconductivity (MoN) 13 , high-energy density (LiN 3 , NaN 3 ) 14 , and high hardness (WN 2 ) 15 , as well as extraordinary chemical and thermal stability (Xe-N) 16 . These nitrides aroused our significant interest in the field of exploring new HP nitrogen species and their potential remarkable properties.…”
Section: Introductionmentioning
confidence: 99%
“…In order to systematically explore the possibility of obtaining new stable N-rich iron nitrides, and especially to examine the possibility of attaining new nitrogen species at HP, we here present extensive structure searches of stoichiometric Fe-N compounds under various pressures ranging from 0 to 300 GPa, using an unbiased particle swarm optimization (PSO) algorithms for crystal structure predictions 18 . This swarm-intelligence high-throughput searching has proven effective in revealing new compositions favorable to form in large sets of multicomponent Ca-H, Li-B, Xe-N, Cs-N systems 16 , 17 , 19 , 20 . The effectiveness has been also demonstrated by recent successes in predicting high-pressure structures of various systems, and their several experimental confirmations 21 30 .…”
Section: Introductionmentioning
confidence: 99%
“…S5 ) indicating that the molecular N-N bond is weakening. Up to highest pressure studied (180 GPa) we see no evidence of Xe-N bonded compounds predicted by theory 24 . In an attempt to promote synthesis of such compounds, we performed laser heating of the sample to temperatures of 3000 K at 120, 150, 160 and 180 GPa but no transition was observed in either Raman spectroscopy or x-ray diffraction.…”
mentioning
confidence: 53%
“…The direct reaction of N 2 and Xe would seem unlikely due to the relative inertness of both materials. Nevertheless, a recent theoretical study predicts the formation of novel xenon nitride compounds above 146 GPa with stoichiometry - XeN 6 24 . Possible interactions between Xe and N 2 have been explored experimentally at low pressures investigating mutual solubility 25 26 .…”
mentioning
confidence: 99%
“…Increased reactivity of the noble gas elements under pressure has been seen in numerous CSP studies [46][47][48][49][50] and for the purpose of this section, xenon was found to react with either iron or nickel at inner core pressure and temperature conditions [46] . Xenon is predicted to form XeM 3 compounds with either metal, which are in parts stabilised by charge transfer from xenon to iron or nickel.…”
Section: Volatiles In Iron-rich Coresmentioning
confidence: 74%